Non-gaussian diffusion model for phosphorus in silicon heavy-doped junctions - Wirbeleit, Frank (Diffusion Fundamentals, 2009)
Besides common implant techniques, dopant diffusion enables steep diffusion profiles in heavily doped deep-source drain and ultra-shallow junctions as required in advanced microelectronic technology. Experimental phosphorus dopant diffusion profiles in silicon are described by a rational function diffusion (RFD) model, based on direct solution of Fick’s equations and suitable for actual work in junction engineering.